Parametric study of wall-mounted annular ring fins for heat transfer enhancement in a flat-bottom cookstove using CFD - Wongkalasin, Komsan; Sonasang, Somchat; Summatta, Chuthong (Creative Science, 2026)
Flat-bottom biomass cookstoves, widely used in developing countries, typically achieve thermal efficiencies below 20% because most combustion energy is lost with the exhaust gas before reaching the pot. Enhancing convective heat transfer at the pot wall therefore represents the most direct pathway to improved efficiency. Although annular fins are well-established passive heat transfer enhancers in industrial heat exchangers, their geometric design space remains unexplored within cookstove combustion chambers. This study addresses that gap through a parametric computational fluid dynamics (CFD) investigation of wall-mounted ring fins in a flat-bottom biomass cookstove. A three-dimensional steady-state CFD model, developed in ANSYS Fluent using the SST k–ω turbulence model with enhanced wall treatment, was validated against measured temperatures at three vertical levels and the chimney outlet. The model showed close agreement at the outlet (2.21% error), while larger discrepancies at the interior levels (16–28%) were attributed to the simplified uniform-inlet boundary condition. Using a one-factor-at-a-time design, thirteen configurations were evaluated across four geometric parameters: fin height, blockage ratio, tier count, and installation height. Fin height showed a non-monotonic effect, with thermal performance peaking at a moderate height before excessive blockage limited further gains. Tier count showed a monotonic trend, reaching a thermal performance factor (TPF) of 1.118 with three tiers. Installation height emerged as the most influential parameter: a single fin positioned near the hot gas inlet achieved the highest performance, with a TPF of 1.138, corresponding to a 14.1% increase in heat transfer to the pot at a pressure-drop penalty of only 0.68%. These findings identify axial position as the primary parameter governing thermal performance. A single fin near the hot inlet offers a low-cost, retrofit-ready route to higher cookstove efficiency, aligned with Sustainable Development Goal 7. GRAPHICAL ABSTRACT HIGHLIGHTS Annular ring fins welded to the inner wall of a flat-bottom cookstove are proposed as a passive heat transfer enhancement strategy. A parametric CFD study covering 12 fin configurations plus a baseline examines the effects of fin height (20–50 mm), number of tiers (1–3), and installation height. Blockage ratios of 0.20–0.50 are evaluated using the SST k-ω turbulence model with enhanced wall treatment in ANSYS Fluent. Thermal Performance Factor (TPF) is used to identify the optimal configuration balancing heat transfer enhancement against pressure drop penalty.